Dietary macronutrient regulation of acyl and desacyl ghrelin concentrations in children with Prader‐Willi syndrome (PWS). (20th July 2020) - Alsaif, Maha; Pakseresht, Mohammadreza; Mackenzie, Michelle L.; Gaylinn, Bruce; Thorner, Michael O.; Freemark, Michael; Field, Catherine J.; Prado, Carla M.; Haqq, Andrea M.
Abstract: Background: The effects of dietary macronutrients on orexigenic and anorexigenic hormones in children are poorly understood. Objective: To explore effects of varying dietary macronutrients on appetite‐regulating hormones [acyl ghrelin (AG) and desacyl ghrelin (DAG), glucagon‐like peptide 1 (GLP‐1), peptide tyrosine tyrosine (PYY) and insulin] in children with PWS and healthy children (HC). Design: Randomized, cross‐over experiments compared two test diets [high protein‐low carbohydrate (HP‐LC) and high protein‐low fat ( HP‐LF) ] to a STANDARD meal (55% carbohydrate, 30% fat, 15% protein). Experiment 1 included ten children with PWS (median age 6.63 years; BMI z 1.05); experiment 2 had seven HC (median age 12.54 years; BMI z 0.95). Blood samples were collected at baseline and at 60‐minute intervals for 4 hours. Independent linear mixed models were adjusted for age, sex and BMI z ‐score. Results: Fasting and post‐prandial AG and DAG concentrations are elevated in PWS children; the ratio of AG/DAG is normal. Food consumption reduced AG and DAG concentrations in both PWS and HC. GLP‐1 levels were higher in PWS after the HP‐LC and HP‐LF meals than the STANDARD meal ( P  = .02‐0.04). The fasting proinsulin to insulin ratio (0.08 vs 0.05) was higher in children with PWS ( P  = .05) than in HC. Average appetite scores in HC declined after all three meals ( P  = .02) but were lower after the HP‐LC and HP‐LF meals than the STANDARD meal. Conclusion: Altered processing of proinsulin and increased GLP‐1 secretion in children with PWS after a high protein meal intake might enhance satiety and reduce energy intake.